2020
DOI: 10.3390/cancers12020288
|View full text |Cite
|
Sign up to set email alerts
|

Novel Genetic Variants of ALG6 and GALNTL4 of the Glycosylation Pathway Predict Cutaneous Melanoma-Specific Survival

Abstract: Because aberrant glycosylation is known to play a role in the progression of melanoma, we hypothesize that genetic variants of glycosylation pathway genes are associated with the survival of cutaneous melanoma (CM) patients. To test this hypothesis, we used a Cox proportional hazards regression model in a single-locus analysis to evaluate associations between 34,096 genetic variants of 227 glycosylation pathway genes and CM disease-specific survival (CMSS) using genotyping data from two previously published ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…We demonstrated that perturbations of CLR expression profiles could be triggered directly by melanoma cells but also indirectly through melanoma-derived supernatants, suggesting that melanoma tumor cells displayed and released glycans that may interact with DCs through CLR molecules. Indeed, it has been shown that melanoma tumor cells exhibited a high ganglioside diversity ( 74 ), displayed alterations in the glycosylation pattern of glycoproteins and glycolipids ( 57 , 58 ), and perturbations of enzymes involved in glycosylation/deglycosylation processes ( 56 ). The impact of tumor-associated glycans on DCs in the context of melanoma remained unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated that perturbations of CLR expression profiles could be triggered directly by melanoma cells but also indirectly through melanoma-derived supernatants, suggesting that melanoma tumor cells displayed and released glycans that may interact with DCs through CLR molecules. Indeed, it has been shown that melanoma tumor cells exhibited a high ganglioside diversity ( 74 ), displayed alterations in the glycosylation pattern of glycoproteins and glycolipids ( 57 , 58 ), and perturbations of enzymes involved in glycosylation/deglycosylation processes ( 56 ). The impact of tumor-associated glycans on DCs in the context of melanoma remained unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Disruption of the Dectin 1galectin 9 axis reprogrammed efficient T-cell mediated antitumor immunity. Melanoma tumor cells exhibit many CLR ligands and display aberrant glycosylation patterns (56)(57)(58), yet the impact of such tumor glyco-code on the CLR machinery of DCs remains unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…LCSCs with a specific phenotype are believed to promote HCC relapse, metastasis, and chemoresistance. Recent studies have shown that aberrant glycosylation of signaling pathways and LCSC markers directly impacts key processes that maintain cell survival, self-renewal, and extravasation properties (31)(32)(33). This study focused on the importance of glycosylation in promoting the stemness of HCC by assessing alterations in somatic mutations, immune cell infiltration, and clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that ALG8 could be a variate of prognostic model for gastric adenocarcinoma (51) and frequently amplified hotspot on 11q14.1 (ALG8) associated with significantly worse prognosis for breast cancer (52). The ALG6 single-nucleotide polymorphism (SNP) is a potential prognostic biomarker for cutaneous melanoma and is likely through modulating gene expression (53). Hsu et al (54) demonstrate that EMT enriched programmed death-ligand 1 (PD-L1) in cancer stem-like cells by the EMT/b-catenin/STT3/PD-L1 signaling axis, in which EMT transcriptionally induced N-glycosyltransferase STT3 (including isoforms STT3A and STT3B) through b-catenin, and subsequent STT3-dependent PD-L1 N-glycosylation stabilized and upregulated PD-L1.…”
Section: Discussionmentioning
confidence: 99%